O processo de aprendizagem do(a) aluno(a) com transtorno do espectro do autismo (TEA) - Silva, Ana Maria da Conceição (2022)
The current research, The teaching and learning process of student with autism spectrum disorder (ASD), presented to the Stricto Sensu Education Post Graduate Program of the Pontifical Catholic University of Goiás (PUC-GO), School of Teachers and Humanities Formation, in the research line “Theories of Education and Pedagogical Processes”, had the general goal of explaining how the pedagogical process of learning of the student with ASD develops. The theoretical foundation that guided this research were the cultural-historical theory and defectology of Vigotski and also the learning theory of Skinner. From these authors, we use Vygotsky's conception of learning, while in Skinner we stick only to specific categories of his theory, such as directed instruction and the reinforcing stimulus. This is a qualitative field research. The procedure for data collection was the semi-structured interview, conducted online, via Google meet and Whatsapp. The research field was formed by six schools in the municipality of Goiânia, being four public schools, one private school and one specialized school. The subjects researched were twelve teachers and twelve mothers of students with ASD who attend elementary school. Firstly, the study provides a description of the characterization of autism from the point of view of theorists such as Kanner, Gillberg, Wing, Asperger and Rutter, making a theoretical review of the concept of autism and presenting characteristics and symptoms of the disorder according to theorists and as described in health manuals. In the second moment, it discusses how learning and cognitive development occurs from both Vygotsky's cultural-historical perspective and Skinner's behaviorist perspective. Then, it presents the theoretical and empirical analysis of the affective and cognitive development of autistic people in their learning process. The results of the research, compiled from interviews with mothers and teachers, showed that certain factors compromise, while others contribute to the process of teaching and learning of the autistic student, both at home and at school. The compromising factors are related to sensory reactivity, communication and language deficits, and repetitive behaviors that the autistic individual presents, impairing attention and focus by generating anxiety, nervousness, agitation and crises. As for the factors that contribute to learning, these are related to the need to promote an affective environment, to organize the didactic material in a few steps and with objective instructions, to make use of reinforcers, to know the student's zone of development, and, finally, to stick to the appropriate form of mediation according to the student's specificities.